THE IMPACT OF THE COVID-19 PANDEMIC ON THE DIGITALISATION OF CRIMINAL PROCEEDINGS (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines the impact of the COVID-19 pandemic on the digitalisation of criminal proceedings. The pandemic exposed significant institutional and technological vulnerabilities in justice systems worldwide, including difficulties in ensuring the continuity of judicial and investigative activities under restrictive conditions. At the same time, it accelerated the introduction of digital tools, online procedures, remote communication mechanisms, and elements of virtual justice. The article argues that digital transformation in criminal proceedings is not merely a technical response to crisis conditions, but an important legal and institutional requirement aimed at ensuring access to justice, procedural efficiency, transparency, and the rule of law. Particular attention is paid to the need for the consistent development of digital technologies in criminal justice and the improvement of criminal procedural legislation in accordance with modern digital realities.
Keywords: COVID-19 pandemic; criminal proceedings; digitalisation; digital transformation; criminal justice; judicial system; investigative activities; virtual courts; access to justice; rule of law.